2021
DOI: 10.3389/fmed.2021.757655
|View full text |Cite
|
Sign up to set email alerts
|

Altered Peripheral Immune Profiles in First-Episode, Drug-Free Patients With Schizophrenia: Response to Antipsychotic Medications

Abstract: Previous research has demonstrated aberrations in the levels of inflammatory cytokines in patients with schizophrenia (SCZ), but most of the respective studies have tested a narrow set of inflammatory cytokines. Here, we aimed to analyze broad immune profiles in the peripheral blood of the first-episode drug-free (FEDF) patients with SCZ at baseline and after an 8-week treatment with atypical antipsychotics. Serum samples from 24 FEDF patients with SCZ and 25 healthy control (HC) subjects were tested using Lum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…At this point, prenatal exposure to inflammation may restrain brain development resulting from structural changes in the volume of gray matter that can cause permanent neural circuits to fail to mature or bring neuroendocrine changes, thus elevating the risk of ADHD [ 95 ]. In addition, the interaction of the HPA axis with a chronic increase in cytokine signals in the immune system during developmental processes is associated with the pathogenesis of ADHD [ 96 ]. However, these serological changes in inflammatory cytokines tend to wane or become reversed along with advances in the age of ADHD patients.…”
Section: Potential Inflammatory Biomarkers In Adhdmentioning
confidence: 99%
“…At this point, prenatal exposure to inflammation may restrain brain development resulting from structural changes in the volume of gray matter that can cause permanent neural circuits to fail to mature or bring neuroendocrine changes, thus elevating the risk of ADHD [ 95 ]. In addition, the interaction of the HPA axis with a chronic increase in cytokine signals in the immune system during developmental processes is associated with the pathogenesis of ADHD [ 96 ]. However, these serological changes in inflammatory cytokines tend to wane or become reversed along with advances in the age of ADHD patients.…”
Section: Potential Inflammatory Biomarkers In Adhdmentioning
confidence: 99%
“…Extensive studies have been carried out on the change of the IL-2 level in patients with schizophrenia. However, the results of these studies vary largely, with some studies showing an increase in the level of IL-2 in in patients with schizophrenia [ 12 , 13 , 14 ], while some found a decrease [ 60 , 61 ] or no change [ 62 ]. There seems to be no generally accepted explanation for this inconsistency, and many possible reasons could contribute to it that may be related to race, disease time, disease process, disease severity and the selection of control.…”
Section: Possible Effects Of Il-2 In Schizophreniamentioning
confidence: 99%
“…Interleukin-2 (IL-2) is a growth factor regulating the autocrine of T-cells (regulatory T, Treg) that plays a role in the immune response [ 11 ]. A large number of studies have shown that IL-2 levels are different in patients with schizophrenia when compared with the healthy control group [ 12 , 13 , 14 ]. This difference is thought to be related to inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…At this point, prenatal exposure to inflammation may restrain brain development resulting from structural changes in the volume of gray matter that can cause permanent neural circuits to fail to mature or bring neuroendocrine changes, thus elevating the risk of ADHD [95]. Also, interaction of the HPA axis with chronic increase of cytokine signals in the immune system during developmental processes is associated with the pathogenesis of ADHD [96]. However, these serological changes of inflammatory cytokines tend to wane or become reversed along with advances in age of ADHD patients.…”
Section: Categorymentioning
confidence: 99%